Computation of Electric Wind Parameters in Direct Current Corona Field - Gudzinskas, J.; Marčiulionis, P.; Žebrauskas, S. (Elektronika ir Elektrotechnika, 2011)
Digital model for analysis of two-dimensional direct current corona field and induced electrohydrodynamic air flow field in wire-to-plane electrode system is discussed. Finite-difference method in polar coordinate system is used for corona field computation. Results of computation of corona field are checked by comparison of digital and experimental data of current-voltage characteristics. Maximum difference of these values of linear current density is 150 µA/m corresponding to the voltage value of 7 kV. The digital model of EHD air flow field consists of finite-difference approximation of the Navier-Stokes equation and the continuity equation in Cartesian coordinates. Check of digital velocity values by comparison of these values with the experimental ones is only qualitative because of the distortion of corona field and air flow field by the probe of hot-wire anemometer. Ill. 6, bibl. 6 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.275